PEMUTUSAN HUBUNGAN KERJA KARYAWAN PERJANJIAN KERJA WAKTU TERTENTU (PKWTT) OLEH PT.DUTA SARANA PERKASA – KABUPATEN BOGOR. (ANALISIS PUTUSAN MAHKAMAH AGUNG NOMOR 791 K/PDT.SUS- PHI/2023) - Sembiring Kembaren, Evo Jumpangena; Sari, Indah (YAYASAN PENDIDIKAN DAN PELAYANAN KESEHATAN, 2024)
Unilateral termination of employment often occurs due to lack of good communication between employers, workers and the government. In this research the author examines and analyzes the Supreme Court Decision Number 791 K/Pdt.Sus-PHI/2023 which adjudicates and examines disputes between workers and PT. Sarana Perkasa Ambassador- Bogor Regency.In this case, the company unilaterally terminated employment relations with employees with an indefinite work agreement (PKWTT), and was not willing to pay severance pay, long service award money and compensation for rights in accordance with article 40 paragraphs (2), (3) and paragraphs (4) Government Regulation no. 35 of 2021. Even though the mechanism for terminating employment relations has been regulated in Article 151 of Law No. 11 of 2020 concerning Job Creation, industrial relations disputes often occur. This research uses normative juridical methods, by analyzing the Supreme Court decision Number 791 K/Pdt.Sus -PHI/2023, through a statutory approach and a case approach. The research results show that First, the mechanism for terminating employment relations carried out by PT. Duta Sarana Perkasa violated statutory regulations. Second, in its decision, the Supreme Court annulled the PHI Bandung decision, on the grounds that it had misapplied the law, and in adjudicating itself regarding judex facti and the reasons submitted by the workers, especially related to status. employees and the rights that workers must receive if they are laid off in accordance with applicable laws and regulations, the author sees that there are legal norms that are ignored by the Panel of Judges regarding processing wages which are not stated in the decision, processing wages that workers should be able to receive after decision determined by the Supreme Court.